A Systems Dynamic Approach for Modeling Policy of Dairy Cattle Development in Indonesia - Priyono Priyono; Rita Nurmalina; Burhanuddin Burhanuddin; Nyak Ilham (Indonesian Center for Animal Research and Development, 2022)
Most farmers conduct small-scale dairy farming in Indonesia, so the appropriate policies are required for its development. Problems in the development of dairy farming in Indonesia cannot be solved partially but need to be solved holistically from the upstream-downstream subsystem. Existing conditions indicate that the rate of milk consumption has not been followed by milk production, so imports are still required. This paper aims to describe a systems dynamic approach model to obtain policy recommendations for dairy farming development in Indonesia. The development of the dairy cattle population and milk production in the four periods of the strategic plan of the Ministry of Agriculture for the period 2000-2019 and the development of the dairy cattle population and milk production in Indonesia for the period 2000-2021 showed positive growth. In the same period, the share of the dairy cattle population was 98.47%, and milk production was 98.93% in Java. Problem-solving in dairy cattle development has been modeled by researchers using a systems dynamic approach. Policy recommendations for dairy farming development using a system dynamic approach: good dairy farming practices, optimizing local resources, empowering farmers and institutions, utilizing appropriate technology, controlling productive dairy cows slaughter, strengthening dairy cooperatives, training for farmers, increasing business scale, and imports of dairy cows. However, improving a holistic model from the upstream to downstream subsystems is still necessary to provide alternative policy recommendations for dairy farming development in Indonesia.